Geopolitical Fragmentation and Capital Allocation - Wohlrab, David (2026)
This thesis examines the impact of geopolitical distance on international capital allocation. The objective is to verify whether and through which mechanisms political divergence between countries systematically influences investment decision-making. The theoretical part establishes the conceptual framework of international capital flows, including the Lucas Paradox and Home Bias, and introduces gravity models as an analytical tool. The empirical part employs a triangulated approach across three levels: the macro level synthesizes gravity models documenting a 15% decline in foreign direct investment and a 25% decline in portfolio investment with increased geopolitical distance; the meso level analyzes German outward investment with emphasis on anticipatory capital withdrawal from Russia; the micro level applies a Black-Litterman model with geopolitical adjustments to a simulated portfolio. The results suggest that geopolitical distance operates as a structural friction complementing traditional determinants of capital flows. The primary value of the geopolitical approach lies in risk identification rather than return prediction.